2016
DOI: 10.1055/s-0036-1584197
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Temporal Bone Fractures

Abstract: Traumatic injury to the temporal bone can lead to significant morbidity or mortality and knowledge of the pertinent anatomy, pathophysiology of injury, and appropriate management strategies is critical for successful recovery and rehabilitation of such injured patients. Most temporal bone fractures are caused by motor vehicle accidents. Temporal bone fractures are best classified as either otic capsule sparing or otic capsule disrupting-type fractures, as such classification correlates well with risk of concom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 87 publications
1
30
0
Order By: Relevance
“…Studies report immediate onset of facial paralysis in 27% of cases while the remaining 73% had delayed onset of facial paralysis among patients with temporal bone fractures. 13,19 The chi-squared test also indicated that there was no statistical difference between the observed frequencies in the present study with the expected frequency reported by the earlier studies. The onset of immediate facial paralysis could be due to nerve stretching/compression by bone spicule(s) or fracture fragment/crushing/division.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Studies report immediate onset of facial paralysis in 27% of cases while the remaining 73% had delayed onset of facial paralysis among patients with temporal bone fractures. 13,19 The chi-squared test also indicated that there was no statistical difference between the observed frequencies in the present study with the expected frequency reported by the earlier studies. The onset of immediate facial paralysis could be due to nerve stretching/compression by bone spicule(s) or fracture fragment/crushing/division.…”
Section: Discussionsupporting
confidence: 68%
“…Female drivers are, by and large, less rash and more cautious than the risk-taking behavior by male drivers while driving. 12,13 There are other reports that highlighted that males are three to four times more prone to trauma than females while driving. [14][15][16][17] Different age groups of people have different exposure risk.…”
Section: Discussionmentioning
confidence: 98%
“…Otic capsule disrupting fractures are highly associated with sensorineural hearing loss, facial nerve paralysis, nerve disruption, CSF leaks and fistulae, and intracranial complications. Otic capsule sparing fractures, although generally associated with conductive or mixed hearing loss, impart a better neurological outcome [15]. Temporal fracture in our case spared the otic capsule, resulting in no hearing loss or facial palsy, demonstrating that the presence of complex temporal trauma may not be the inciting event for neurological sequelae.…”
Section: Discussionmentioning
confidence: 54%
“…Temporal fractures are typically divided into two categories relative to the petrous ridge: transverse or longitudinal [15]. However, most cases, including the case herein, cannot be clearly delineated in this manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation